THE INFLUENCE OF ACCOUNTING PRINCIPLES ON THE TENDENCY OF FINANCIAL REPORT MANIPULATION: A BEHAVIORAL THEORY PERSPECTIVE - Rita J D Atawarman; Helita Resley; Vannia F Siahaya; Anita Ipa (PT. Jurnal Center Indonesia Publisher, 2026)
Financial statement manipulation persists despite the application of accounting principles. This study aims to analyze the influence of accounting principles on the tendency of financial statement manipulation from a behavioral theory perspective. A Systematic Literature Review was conducted on 30 national and international articles published between 2014 and 2024. The results indicate that flexibility in accounting standards and subjective judgment increase the likelihood of earnings management, which is influenced by performance pressure and incentive systems. This study emphasizes the importance of consistent accounting principles and behavioral control in reducing financial statement manipulation.